JOURNALISTIC DISCOURSE AS A SPECIAL TYPE OF DISCOURSE - E. A. Sidelnikova (Гуманитарные и юридические исследования)
The multiaspect study of integration and interaction processes between economics and linguistics contributed to the journalistic economic discourse research as a different genre, thematically diverse text area and a type of institutional communication. In the process of analysis of cognitive and pragmatic essence of the journalistic economic discourse and cognitive background of its study, i.e. reflection of economic events in a language, presentation of language integrity as a system of signs that is revealed in the course of economic activity, the author consistently proves that the economic discourse in the journalistic texts is interpreted as a hyponym of the business discourse, and works out its definition.